Does Okun's law and its coefficient value, Ø exist? Evidence from sixteenth South and Southeast Asian countries during 1991-2020 - Abdus Samad (Global Business & Finance Review (GBFR), 2023)
Purpose: This paper retested the Okun's Law established in the 1960s and the subsequent research on Okun's findings that a 1% increase in unemployment would lead to a 3 % decrease in GDP), i.e. Okun's coefficient (Ø)= -3 in diverse economies of sixteen South and Southeast Asia, sixteen countries. Design/methodology/approach: Using panel data in two models, the first difference model: (Yt -Yt-1) = » - Ø(Ut -Ut-1) and the gap model: (Yt -Y^ ,) = » - Ø(Ut -U^ ) were estimated. Findings: Results of pool ordinary least square (POLS), Fixed Effect Model (FEM), and Random Effects Model (REM) supports Okun's Law and shows that the coefficient, Ø, is (-4.4) suggesting that every 1 percent unemployment rate leads to 4.4 decrease in GDP. The Okun's coefficient varies with country. The validity of Okun' coefficient, Ø= -2 percent, is found only in four. Findings of negative coefficient and its significance provides important policy prescriptions for nine countries. Research limitations/implications: This paper suffers from limitations. First data limitation. This paper used annual data of 30 years. Future research may include quarterly data or annual data with more observations. Second, as Hodrick and Prescott [1997] filtering approach suffers from criticism, Cobb-Douglas production function estimate may be applied for estimating full-employment GDP and natural rate of unemployment. Originality/value: All studies of Okun's law studies derived its coefficient focused on the economically developed countries, this study is an exception. The survey of literature shows that there is no research of Okun's for sixteen South and Southeast Asian countries with diverse level of economic growth. So, the result of this study is an important contribution in the literature of Okun's law. Second, as the policy makers of these countries are facing mounting pressure of unemployment, finding the value of Okun's coefficient is a contribution of this paper for them.
Keywords: 650; Okun's Law; Panel Estimates; Fixed Effect Model; South and Southeast Asia